2022
DOI: 10.3389/fphar.2022.1036506
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoid natural products exert neuroprotection via the PI3K/Akt pathway

Abstract: PI3K/Akt, an essential signaling pathway widely present in cells, has been shown to be relevant to neurological disorders. As an important class of natural products, terpenoids exist in large numbers and have diverse backbones, so they have a great chance to be identified as neuroprotective agents. In this review, we described and summarized recent research for a range of terpenoid natural products associated with the PI3K/Akt pathway by classifying their basic chemical structures of the terpenes, identified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 126 publications
0
4
0
Order By: Relevance
“…Numerous studies have shown that the PI3K/Akt signaling pathway can inhibit neuronal apoptosis and promote neuronal growth [ 59 ]. Akt is a key protein in the PI3K/Akt pathway, and phosphorylated Akt further activates downstream proteins that participate in cell growth and development processes [ 60 ]. Following a stroke, the PI3K Akt pathway maintains brain homeostasis by regulating various target proteins; is an important pathway for protecting brain nerves [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that the PI3K/Akt signaling pathway can inhibit neuronal apoptosis and promote neuronal growth [ 59 ]. Akt is a key protein in the PI3K/Akt pathway, and phosphorylated Akt further activates downstream proteins that participate in cell growth and development processes [ 60 ]. Following a stroke, the PI3K Akt pathway maintains brain homeostasis by regulating various target proteins; is an important pathway for protecting brain nerves [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…It crosses the blood–brain barrier and inhibits microglial activations (Siddique, 2021). Another phenolic compound, polydatin, is used in neurodegenerative diseases and inhibits the PI3K/AKT pathway (Xu et al., 2022). The natural polyphenolic stilbene derivative, Resveratrol, plays a role in neurodegenerative disorders and stimulates AMPK (AMP‐activated protein kinase) and autophagy pathway (Andrade et al., 2018).…”
Section: Therapeutic Approaches Targeting Autophagy and Proteostasismentioning
confidence: 99%
“…Based on the number of repeating units, terpenes, and terpenoids are generally classified into mono‐ (C10), sesqui‐ (C15), di‐ (C20), tri‐ (C30), tetra‐ (C40), and polyterpene (C > 40) (W. Yang, Chen, et al, 2020). Of various underlying mechanisms pertinent to their health‐beneficial activities, particularly in cancer settings, modulation of the PI3K/Akt pathway is of special notice (El‐Baba et al, 2021; B. Xu et al, 2022; Q. Yang et al, 2021).…”
Section: Phytochemicals Affecting Pi3k/akt/mtor Signaling Pathway To ...mentioning
confidence: 99%
“…. Of various underlying mechanisms pertinent to their health-beneficial activities, particularly in cancer settings, modulation of the PI3K/Akt pathway is of special notice (El-Baba et al, 2021;B. Xu et al, 2022;Q.…”
mentioning
confidence: 99%